The buffalo (Bubalus bubalis) as a reservoir of Babesia bovis, B. bigemina and Anaplasma marginale in Western Cuba - Álvarez, Dasiel Obregón; González, Belkis Corona; Zamora, Pastor Alfonso; López, Yoandri Hinojosa; Valdez, Yasmani Armas; López, Eugenio Roque; Sánchez, Adrian Díaz; Marrero, Siomara Martínez; Cañizares, Ernesto Vega; Fonseca, Adivaldo Henrique; Oliveira, Marcia Cristina; Machado, Rosangela Zacarias [UNESP]; et al. (My University, 2019)
In the present work, the high prevalence of coinfection by Babesia bovi s, B. bigemina and A. marginale in buffaloes is reported for the first time and the presence of Babesia bigemina is diagnosed in buffaloes from Western Cuba. Subclinical infections by B. bovis , B. bigemina and A. marginale were diagnosed in buffaloes and several epidemiological characteristics of these infections in buffalo herds were analyzed, specifically, the factors related to the participation of the buffalo species as a reservoir of these pathogens in the livestock conditions of the western region of the country. It was demonstrated that there is genetic similarity in the msp 1α gene between A. marginale isolates from cattle and buffalo, which suggests that both host species are connected in the transmission chain of this rickettsia. It was concluded that bubaline herds have reservoir capacity for B. bovis , B. bigemina and A. marginale and that, together with the populations of R. microplus and bovine herds, they make up the reservoirs of these hemoparasites in the livestock ecosystems of Cuba. . The results demonstrate the need to include buffaloes in the surveillance and control programs of these hemoparasites.
El búfalo (Bubalus bubalis) como reservorio de Babesia bovis, B. bigemina y Anaplasma marginale en el Occidente de Cuba
Keywords: A. marginale; B. bigemina; B. bovis; bubalines; co-infections; Cuba